Cannot investors really price the book-tax differences correctly? Evidence from accelerated depreciation policies - Hang Liu; Yichao Zhao (China Journal of Accounting Studies (CJAS), 2022)
Extensive studies have found that investors misprice book-tax differences (BTDs). We take the accelerated depreciation policies of fixed assets implemented in China since 2014 as the research setting and investigate the following issues: When a temporary BTD is generated due to the tax preferential policies of accelerated depreciation, and the temporary BTD disclosed in financial statements can be clearly understood by investors, will investors still misprice it? We find that accelerated depreciation policy-induced temporary BTD (AccBTD) and other temporary BTD (OthBTD) are both informative. Furthermore, investors could correctly price AccBTD while misprice OthBTD. Finally, active institutional investors and analysts can promote the correct pricing of AccBTD but cannot alleviate the mispricing of OthBTD. Overall, our evidence suggests that investors do not always misprice BTDs. Specifically, when we decompose the specific components of BTDs and control the measurement errors effectively, we will have completely different findings.
Keywords: 650; Book-tax differences; temporary book-tax differences; asset pricing; market anomalies; accelerated depreciation